THE INTERPERSONAL MEANING OF MOCKING CHANT TO FOOTBALL PLAYERS BY ENGLISH PREMIER LEAGUE SUPPORTERS - Fatoni, Nur Rochman; Santosa, Riyadi; Djatmika, Djatmika (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
The discussion of the social relationship meaning between participants in language interaction, particularly spoken, is interesting. Sport domain,Â one of the discourse that close to the social community, is still rarely uncovered in language research. This research highlights the interpersonal meaning of the mocking chant to football players sung by supporters of the English Premiere League (EPL), especially from the 6 biggest clubs (the big six). It uncovers interpersonal meaning through the analysis of the MOOD system, modality, and polarity within the Systemic Functional Linguistic approach. It is a qualitative descriptive study using content analysis. The data are clauses taken from the â€˜football player-mockingâ€™ chant lyrics from the supporters of the big six clubs. The analysis results are obtained through domain, taxonomy, componential and cultural themes analysis. MOOD system analysis shows an equal position between supporters and listeners. It is also supported the finding that the information exchanged in the discourse are about events or disgrace of the mocked players. Eventhough, it must be noted that the mocked players are positioned at different points of view because of the negative value of the polarity. The modality analysis shows the confidence of supporters when singing the mocking chant to the players.